PENGARUH MEKANISME CORPORATE GOVERNANCE,AUDIT TENURE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DAN INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan BUMN yang terdaftar di BEI Tahun 2014-2018) - Anistya Vinta Desi (Pascasarjana Universitas Sultan Ageng Tirtayas, 2022)
The study was conducted in order to find out the effect of corporate governance mechanisms by proxying the size of board and independent board, audit tenure and company size on earnings management and financial statement integrity of BUMN companies listed on the Indonesia Stock Exchange that published financial statements for the period 2014-2018 . By using purposive sampling technique, 65 company samples were obtained and analyzed using multiple linear regression. The results of this study indicate that (1) Size Board has a positive effect on the integrity of financial statements (2) Independent board does not affect the integrity of financial statements (3) Audit Tenure does not affect the integrity of financial statements (4) Firm size does not affect the integrity of the report finance (5) Earnings management does not affect the integrity of financial statements (6) Size Board has a positive effect on earnings management (7) Independent Board has no effect on earnings management (8) Audit Tenure has positive effect on earnings management (9) Size of company influences positive towards earnings management (10) Size Board influences the integrity of financial statements mediated by earnings management variables (11) Independent Board influences financial statement integrity is not mediated by earnings management variables (12) Audit Tenure on Integrity of Financial Statements n not mediated by Earnings Management (13) Firm size towards the Integrity of Financial Statements is mediated by Earnings Management variables.